2016
DOI: 10.1055/s-0035-1569288
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Osteocalcin and Insulin Resistance in Patients with Impaired Glucose Tolerance or New-Onset Diabetes Mellitus After Liver Transplantation

Abstract: Liver transplantation (LT) patients are at high risk of developing new-onset diabetes after transplantation (NODAT). Osteocalcin has been proposed as a mediator between bone tissue and glucose metabolism, but its role in the pathogenesis of diabetes is not defined yet. Our objective was to assess the relationship between serum osteocalcin and glucose metabolism parameters in liver transplantation recipients. A total of 187 liver transplantation patients were cross-sectionally studied, 54 of them developed NODA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Domingueti et al (9) demonstrated that the linkages between oxidative stress, inflammation, hypercoagulability, vascular complications and diabetes mellitus have been investigated, and inflammation and oxidative stress may be regarded as predictors for evaluating the risk of cardiovascular and renal complications in patients with diabetes mellitus. In addition, previous studies have investigated the insulin resistance and sensitivity in liver, adipose tissue, skeletal muscle and placenta samples (10)(11)(12). Furthermore, studies have indicated that diabetes mellitus may be a syndrome, which includes vascular dysfunction, insulin resistance, inflammatory responses and oxidative stress (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Domingueti et al (9) demonstrated that the linkages between oxidative stress, inflammation, hypercoagulability, vascular complications and diabetes mellitus have been investigated, and inflammation and oxidative stress may be regarded as predictors for evaluating the risk of cardiovascular and renal complications in patients with diabetes mellitus. In addition, previous studies have investigated the insulin resistance and sensitivity in liver, adipose tissue, skeletal muscle and placenta samples (10)(11)(12). Furthermore, studies have indicated that diabetes mellitus may be a syndrome, which includes vascular dysfunction, insulin resistance, inflammatory responses and oxidative stress (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is prevalent among patients undergoing liver transplantation for hepatitis C virus (HCV) cirrhosis 27 and other causes of liver cirrhosis 28 . A cross-sectional study showed that insulin resistance is highly prevalent and associated with new onset diabetes after liver transplantation 29 . None of these studies reported the impact of insulin resistance on the development of hepatic steatosis after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Sanchez-Enriquez et al demonstrated a link between cardiovascular risk factors for patients with T2DM, including high BMI, high fasting plasma glucose, and high HDL, and low serum levels of uOC, suggesting that osteocalcin could have more physiological roles than previously expected [152]. In a different model, patients who underwent liver transplantation and subsequently became diabetic post-surgery demonstrated that total osteocalcin was, yet again, inversely associated with plasma glucose levels and insulin resistance [153].…”
Section: Targeting the Reduction Of Metabolic Stress: The Bone-pancrementioning
confidence: 98%